MOTIF JEPANG DALAM TOKYO STRATEGY FOR MEKONG-JAPAN COOPERATION PADA TAHUN 2018-2020 - Roza Nafsiah; Mhd. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study analyzes the Japanese Motives In The Tokyo Strategy For Japan-Mekong Cooperation In 2018-2020. The purpose of this study is to find out the bilateral relations between Japan and the Mekong, to find out what Japan's motives are for collaborating in the Tokyo Strategy for Mekong-Japan Cooperation. Then be able to contribute in the form of views to readers regarding cooperation in the Tokyo Strategy for Mekong Japan Cooperation in 2018-2020. This study uses qualitative methods, with data collection techniques through literature studies sourced from several books, journals, articles and internet sites. This study uses the perspective of Liberalism and Foreign Aid Theory. The result of this research is that giving foreign aid by Japan to the Mekong countries through ODA not only as a form of assistance to developing regions, but also for meet Japanese interests. As for the motive for the assistance given, namely, humanitarian motives in the Mekong region by reducing poverty. Economic motives by increasing trade, investment, and export, The identity motive as evidenced by Japan being the country that provides the largest and most consistent foreign aid to the Mekong. And finally, the environmental motive, which is evident from the many environmental programs carried out by Japan on the Mekong. This is considered reasonable considering that Japan is a country that is concerned about global environmental issues. Where Japan is involved in many forums that discuss global environmental issues. Keywords: Motive Japan, Tokyo Strategy, Mekong-Japan Cooperation.